The necessary shift from diagnostic to prognostic research - Dinant, G; Buntinx, F; Butler, C (BioMed Central, 2007)
Background: Do doctors really need to establish an etiological diagnosis each time a patient presents? Or might it often be more effective to treat simply on the basis of symptoms and signs alone, relying on research and on our experience of outcomes for patients who presented in similar ways in the past? Discussion: At a time of increase health care costs especially in pharmaceuticals and expensive diagnostic tests, this article uses examples from recent research to address this question. Our examples come from general practice, because that is where doctors frequently see patients presenting with a yet undifferentiated disease which is consequently difficult to diagnose. The examples include respiratory tract infections, low back pain and shoulder pain. Finally we discuss the 'something is wrong' feeling. Summary: We conclude that, in addition to diagnostic research, a renewed focus on prognostic research is needed.